How shared reality is created in interpersonal communication. (October 2018) - Echterhoff, Gerald; Schmalbach, Bjarne
Highlights: The evaluative tuning of messages to an audience is a key pathway to shared reality. What matters is the goal underlying audience tuning rather than audience tuning per se. Mere message production, communication about commonly known information, grounding, and validation responses contribute to shared reality. Intragroup or serial-chain communication can confirm stereotypes and reinforce shared realities about intergroup relations. Abstract : Communication is a key arena and means for shared-reality creation. Most studies explicitly devoted to shared reality have focused on the opening part of a conversation, that is, a speaker's initial message to an audience. The aspect of communication examined by this research is the evaluative adaptation (tuning) of the messages to the audience's attitude or judgment. The speaker's shared-reality creation is typically assessed by the extent to which the speaker's evaluative representation of the topic matches the audience-tuned view expressed in the message. We first review research on such audience-tuning effects, with a focus on shared-reality goals and conditions facilitating the generalization of shared reality. We then review studies using other paradigms that illustrate factors of shared-reality creation in communication, including mere message production, grounding, validation responses, and communication about commonly known information (including stereotypes) in intragroup communication. The different lines of research reveal the potency, but also boundary conditions, of communication effects on shared reality.